Letter to my Hometown Kalimpong - Bhutia, Anisa (ACME, 2024)
In this letter, I delve into my family history and sharing my grandmother's stories through the tales of this city that is so close to my heart. I take you through my memories of having shared food with neighbors during special occasions. Through my interaction with the place, I show Kalimpong's multiple layers of transformation. With the transformations to the city in mind, I ask us to rethink what future we are looking for and who we are including and excluding in the process. Ultimately, this letter is an ongoing conversation that I am having with my hometown for a better, brighter and more desirable future for everyone.